2015
DOI: 10.1002/hbm.22913
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional amygdala activation and connectivity with the prefrontal cortex in current cocaine users

Abstract: Our findings suggest that amygdala hyperactivity to biologically salient stimuli may represent a risk factor for an early onset of cocaine use and that prolonged cocaine use may further sensitize amygdala activation. High amygdala activation to emotional face processing in current cocaine users may result from low prefrontal control of the amygdala response to such stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…In addition, medial prefrontal-amygdala circuits involved in fear conditioning and extinction have been implicated in persistent drug-seeking behavior and relapses (Crunelle et al 2015 ; Peters et al 2009 ). Interestingly, ventral striatal (VS) high frequency DBS in rats, comparable to the settings often used in humans, impaired extinction training of morphine seeking, whereas low frequency dorsal VS DBS strengthened morphine extinction memory (Martínez-Rivera et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, medial prefrontal-amygdala circuits involved in fear conditioning and extinction have been implicated in persistent drug-seeking behavior and relapses (Crunelle et al 2015 ; Peters et al 2009 ). Interestingly, ventral striatal (VS) high frequency DBS in rats, comparable to the settings often used in humans, impaired extinction training of morphine seeking, whereas low frequency dorsal VS DBS strengthened morphine extinction memory (Martínez-Rivera et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several cue reactivity studies have indeed demonstrated increased amygdala activation in response to substance-related cues, supporting the role of the amygdala in drug-related behavior ( 37 39 ). However, we have recently demonstrated that the amygdala in regular cocaine users is also hyperresponsive to negative emotional stimuli in general ( 40 , 41 ), which is suggested to be normalized by substance intake ( 42 ). However, it is still unclear how the amygdala modulates frontostriatal processing of drug-related cues and how this is related to childhood trauma and negative emotional states.…”
Section: Introductionmentioning
confidence: 99%
“…Participants performed an emotional face matching task, known to probe amygdala and hippocampus activity [31,32]. The block design consisted of the alternated presentation of 2 emotional condition blocks (fearful and angry face expressions) with 3 control condition blocks (blurred ellipses).…”
Section: Fmri Assessment: Emotional Face Matching Taskmentioning
confidence: 99%